Characterizing biomarker features of cognitively normal individuals with ventriculomegaly. Issue 1 (5th September 2017) - Li, Xiaofeng; Ba, Maowen; Ng, Kok Pin; Mathotaarachchi, Sulantha; Pascoal, Tharick A.; Rosa‐Neto, Pedro; Gauthier, Serge
Abstract: Introduction: The clinical significance of ventriculomegaly in cognitively normal elderly individuals remains unclear. Methods: We selected cognitively normal individuals (n = 425) from the Alzheimer's Disease Neuroimaging Initiative database and calculated Evans index (EI) based on the ratio of the frontal horn and skull diameter. We defined ventriculomegaly as EI ≥ 0.30, and the participants were stratified into EI ≥ 0.30 group and EI < 0.30 group. Neuropsychological, imaging, and fluid biomarker profiles between the two groups were then compared using regression models. Results: A total of 96 (22.5%) individuals who had ventriculomegaly performed worse on the cognitive tests; showed smaller hippocampal volume but larger caudate, cingulate, and paracentral gyrus volumes; and displayed lower positron emission tomography [ 18 F]fluorodeoxyglucose standardized uptake value ratio but higher amyloid burden represented by higher [ 18 F]florbetapir standardized uptake value ratio and lower cerebrospinal fluid amyloid β 1–42 levels compared to those without ventriculomegaly. Discussion: Asymptomatic ventriculomegaly might be an early imaging signature of preclinical Alzheimer's disease and/or normal pressure hydrocephalus.